PRELIMINARY NOTE ON THE ISOLATION AND PARTIAL PURIFICATION OF A LYSOZYME IN BUTTERMILK - CASTANEDA AGULLO, M (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1946)
Oral doses of KC1 (01-05 g/kg) were given animals and their convulsive response tested for a period of 2 hrs thereafter Other animals were given orally a total of 125 g/kg in small doses over a 60 hr period The admn of K had no direct or defi
GAC MED MEX
Keywords: PRELIMINARY, ISOLATION, PARTIAL, PURIFICATION , LYSOZYME, BUTTERMILK; CIENCIAS MEDICAS; Medicine, General & Internal